2021
DOI: 10.1002/lary.29526
|View full text |Cite
|
Sign up to set email alerts
|

Role of Body Dysmorphic Disorder in Patients With Postparalytic Facial Synkinesis

Abstract: Objectives/Hypothesis To evaluate the role of body dysmorphic disorder (BDD) in patients with postparalytic facial nerve syndrome with synkinesis (PFS). Study Design A single‐center retrospective cohort study. Methods A total of 221 adults (74% women; median age: 44 years; median duration since onset of facial palsy: 1.6 years) were included. To diagnose BDD, the BDD Munich Module was used. Associations with House‐Brackmann grading, Stennert index grading, Facial Clinimetric Evaluation (FaCE) survey, Facial Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 46 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…A limitation of both questionnaires is the assessment of self-perception of appearance. Since it has been shown that patients with facial palsy may have a higher risk of developing body dysmorphic disorder, it is even more important to capture the appearance from the patient’s point of view 7 . In this context, the patient-reported outcome instrument FACE-Q Paralysis questionnaire, which was developed by Klassen et al in 2020, stands out as a comprehensive tool for capturing the patient’s perspective in the areas of Appearance, Facial Function, Health-related Quality of Life, and Adverse Effect 8 , 9 , The FACE-Q Paralysis is part of the more comprehensive FACE-Q Craniofacial questionnaire, which is an outcome measure designed for patients with visible and/or functional facial distinction 9 .…”
Section: Introductionmentioning
confidence: 99%
“…A limitation of both questionnaires is the assessment of self-perception of appearance. Since it has been shown that patients with facial palsy may have a higher risk of developing body dysmorphic disorder, it is even more important to capture the appearance from the patient’s point of view 7 . In this context, the patient-reported outcome instrument FACE-Q Paralysis questionnaire, which was developed by Klassen et al in 2020, stands out as a comprehensive tool for capturing the patient’s perspective in the areas of Appearance, Facial Function, Health-related Quality of Life, and Adverse Effect 8 , 9 , The FACE-Q Paralysis is part of the more comprehensive FACE-Q Craniofacial questionnaire, which is an outcome measure designed for patients with visible and/or functional facial distinction 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The main problem for patients suffering from facial synkinesis beyond visual disturbances is the inability to properly convey emotions. This in turn can lead to psychological issues, such as depression, social isolation, and anxiety (14)(15)(16)(17)(18). Consequently, facial synkinesis often has a strong negative impact on the quality of life of a patient (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%